Peran Perusahaan dalam Fasilitasi Masjid Diaspora : Studi Kasus Masjid Nusantara Akihabara Jepang - Ahsan, Abid; Thoha, Ahmad Faiz Khudlari; Mauludi (Journal of Islamic Management, 2026)
This research aims to explore the role of a company in facilitating a diaspora mosque by focusing on the case of Masjid Nusantara Akihabara in Japan. Employing a qualitative approach with an intrinsic case study design, data were collected through in- depth interviews, participant observation, and document analysis. The study identifies four key roles of the company: (1) providing free worship space without business interference, (2) engaging company staff as mosque managers, (3) maintaining a transparent and separate financial system for the mosque, and (4) preserving symbolic boundaries between religious and corporate functions. These findings reflect forms of institutional work carried out informally and collectively by internal actors. The study contributes to stakeholder theory by emphasizing value-driven engagement beyond market relations and enriches institutional logic literature through empirical insights into how religious institutions can emerge and sustain themselves within diaspora business environments